Technological Innovations and Degrowth Opportunities From Urban Egypt: Initiating the Discourse - Ibrahim, Sherwat E.; Sarkis, Joseph (Frontiers in Sustainable Cities, 2020)
• Degrowth can support urban sustainability, especially in Global South or developing nations. • Degrowth and technological innovation have had controversial relationships. Some believe they cannot function together, others believe they are supportive. • This debate is evaluated and we posit that they are compatible if managed carefully with effective policies in place. • We provide three technological cases from Egypt, these cases are mapped to degrowth elements. • This is just an initial step in introducing the discourse, degrowth with environmental and social sustainability needs to be included on the map of policy makers. • Policy implications include investment, awareness raising, education, and diffusion of technologies that can support degrowth.